Using Hypnoteaching Method to Improve Learning Motivation and Speaking Skill of The Students of SMAN 3 Pangkajene - Herawati Abuhaer (Qalam : Jurnal Ilmu Kependidikan, 2020)
The objective of this research is to find out whether or not the application of hypnoteaching method’s improve the students’ achievement in speaking skill and to describe whether or not the use of Hypnoteaching trigger students’ motivation in learning Speaking at SMA Negeri 3 Pangkajene. The researcher applied quasi-experimental design. The population of this research is the tenth grade students of SMA Negeri 3 Pangkajene in 2016 / 2017 academic year. The result of data analysis shows that t-test value is greater than t-table value (5.79 > 2.1) at level of significance (p) = 0.05. It means that there is a significant difference of speaking skill between two classes and it indicates that null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. Therefore, based on the findings and discussion of this research, it can be concluded that the implementation of Hypnoteaching method improves students speaking skill. The result of data analysis from the questionnaire shows that 43.75%  students can categorized as strongly motivated students after the treatment. Based on that, the researcher conclude that hypnoteaching can improves student’s motivation in learning speaking.